Assessing The Effects of Television Programs on Students at Essence High School, Kaduna - Wada, Hadiza; Mohammed, Shamsudeen (NIU Journal of Social Sciences; Vol 7 No 3 (2021): KIU Journal of Social Sciences, Vol. 7 No. 3, September 2021, 2021)
Television viewing is still prominent among young people living with their parents. Exposure to some of its programs/contents have however been linked to incidents of social vices such as open violence, illicit sex, drug abuse and other related acts. This study sets out to explore the influence of television viewing on student behavior and academic performance among secondary school students in Kaduna metropolis. The objectives of this study are to determine the level of secondary school students’ exposure to television programs, identify the type of programs/contents that secondary school students view on television and examine the perceptions of secondary school students on the effects of television viewing on their habits and behavior. The theoretical frameworks adopted for this study is Cultivation theory of mass media as advocated by George Gerbner (1976), which proposes that heavy viewers of television are thought to be imbibing attitudes that leads to the belief that the world created by television is an accurate depiction of the real world. A qualitative study, it employed a focus group discussion method to elicit relevant information, including key informant interview. The students of Essence Secondary School, at 10 Kashim Ibrahim Road in Kaduna metropolis, were the targets of the study, but collaborative data were also elicited from parents and teachers. Results show that television viewing does take away from credible academic performance, as well as influence behaviors and actions of the students.